Scheduled Empiric Antibiotics May Alter the Gut Microbiome and Nutrition Outcomes in Pediatric Intestinal Failure. (19th October 2020) - Talathi, Saurabh; Wilkinson, Linda; Meloni, Katie; Shroyer, Michelle; Eipers, Peter; Van Der Pol, William J; Martin, Colin; Dimmitt, Reed; Yi, Nengjun; Morrow, Casey; Galloway, David
Abstract: Background: In this study, we aim to determine the effect of scheduled antibiotics on gut microbiome in pediatric intestinal failure (IF) and to evaluate the effect of the gut microbiome on nutrition outcomes in IF. Methods: Fecal samples were collected at regular intervals from pediatric patients with IF for gut microbiome comparison between 2 cohorts: (group 1) those on scheduled prophylactic antibiotics and (group 2) those who were not on scheduled antibiotics. Gut microbiome composition and diversity were compared among the 2 cohorts. The association among gut microbiome composition, diversity, and nutrition outcomes (mainly ability to decrease parenteral nutrition [PN] energy requirement and ability to attain positive growth) was also determined. Results: The microbiome of patients with IF on scheduled antibiotics differed significantly from those not on scheduled antibiotics. Abundance of certain Gram‐negative and pathogenic bacteria ( Pseudomonas, Prevotella, and Sutterella ) was higher in the scheduled cohort. Patients with decreased Enterobacteriaceae demonstrated a greater ability to demonstrate a reduction in PN requirement, as well as attain positive growth. Conclusion: Scheduled antibiotics may alter the gut microbiome in children IF, which in turn may have an influence on important nutrition outcomes in pediatric IF. Further larger, multicenter studies are needed to determine the effect of scheduled antibiotics on the gut microbiome in this patient population and their overall effect on nutrition outcomes.